Clinical and Immunologic Profile of Women with Recurrent Pregnancy Losses in the Philippine General Hospital: A Retrospective Study from 2010-2015 - Mondragon, Alric; Agcaoili-De Jesus, Maria Socorro; Alentajan-Aleta, Lara Theresa (Philippine Journal of Allergy, Asthma and Immunology, 2022)
Background: Recurrent pregnancy loss (RPL) affects 1-5% of women with most cases due to autoimmune causes and around 40-50% are idiopathic. Commonly associated with RPL is antiphospholipid syndrome (APS). Investigations have revealed that several patients present only with pregnancy morbidities alongside antiphospholipid antibodies (aPL). In the Philippines, the Philippine Obstetrical and Gynecological Society has released its practice guidelines on RPL; however, local studies on RPL have been lacking. Methodology: A retrospective review was performed on both in-patient and outpatient medical records relating to the patients’ pregnancies. Patients included were those referred to the Allergy and Immunology service for suspicion of APS, aPL positivity, or history of pregnancy loss during the period of January 2010 to August 2015 with at least 2 previous spontaneous pregnancy losses and with at least one work-up for aPL. Results: We reviewed the clinical features and immunologic profile of 78 patients with a history of at least two pregnancy losses from 2010 to 2015 followed up at our institution. The mean age of patients was 32.24 ± 5.52 years (range: 20 to 43; median: 34). There was a total of 263 previous pregnancies among the patients, 181 (68.82%) of which were abortions and 43 (16.35%) were preterm deliveries. Comorbidities present in these patients were hypertension (15), diabetes mellitus (DM) (11), asthma (6), Polycystic ovary syndrome (5), and systemic lupus erythematosus (2). Repeat test determination was only done in 18 patients; only three patients fulfilled the Sydney criteria, two in category I, and one in category IIa. Among those with single determination for aPL, 35 were reactive for LAC, 10 for aCL, and 1 for anti-β2GPI. Clinical features were not significantly associated with any obstetric complication. Single positivity of any of the aPLs was not associated with any obstetric complication. Conclusion: This study shows a high incidence of aPL positivity among RPL patients. Although clinical factors such as hypertension and prior late pregnancy losses appeared to have an association with poor obstetric outcomes, these were not significant. Positivity to any of the aPLs also did not have a significant association with obstetric outcomes. Although largely discussed in this study is the connection of RPL and APS, several other unexplained factors of RPL could be involved in the study population.